STUDI PENDEKATAN ALQURAN - Muhammad Roihan Daulay (IAIN Padangsidimpuan, 2014)
Holy Quran is one of the principle resources for making the students to become men of faith and men of god-fearing to Allah SWT. Moreover, by these Holy Quran can make as a basic for doing and in the process of education. Thus, in this case, the writer will try to make some definitions like Holy Quran, Vision from Allah, Phenomenological, and pattern of exclamation of passages of Quran in Holy Quran study.